Nurses’ perceived barriers to and facilitators of pain assessment and management in critical care patients: a systematic review - Amani H. Alhassoon; Nawaf Shaman Alotibi; Amani Thaar Alotibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Pain is a prevalent issue among critically sick cases, with inadequate management of pain documented even though the implementation of pharmaceutical and/or nonpharmacological treatments. Research has demonstrated that the knowledge and attitudes of intensive care unit (ICU) nurses might affect pain evaluation and treatment. Furthermore, obstacles to evaluating and managing pain in the intensive care units, categorized as nurse-related, physician-related, system-related, or patient-related, can influence intensive care unit nurses’ conduct regarding pain evaluation and treatment. Aim and objective: This investigation aims to evaluate the practices of critical care nurses regarding evaluation and dealingwithpain, as well as to investigate the perceived barriers and facilitators associated with evaluating pain in critically sick cases. Patients and methods: A systematic review of literature concerning pain evaluation and treatment in critical care patients has been conducted across four databases, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Conclusion: Inadequate knowledge of dealing with pain and inappropriate attitudes have been identified among nurses due to multiple obstacles and challenges. Regular pain evaluations and therapeutic education courses must be conducted for all nurses in Al-Qassim, Saudi Arabia, particularly for nurses working in intensive care units.